AGRO-ECOLOGICAL CONDITIONS OF SORGHUM PRODUCTIVITY FORMATION IN SOUTHERN REGIONS OF UKRAINE UNDER CLIMATE CHANGE CONDITIONS - Polevoy, A. M.; Bozhko, L. E.; Volvach, O. V.; Barsukova, E. A. (Scientific Progress & Innovations, 2020)
In the previous decade, sorghum has gained an important place among cereals. A great popularity of sorghum is caused by its hardiness to cultivation places, high vital characteristics, not requiring much care and giving high yields. Expanding sorghum areas of spreading requires a thorough justification of the envi-ronmental effect on the crop productivity. The study is based on the materials of long-term observations of sorghum yield and meteorological factors. The peculiarities of sorghum crop formation under different agro-meteorological conditions during the growing season according to observations from 1986 to 2015, as well as the dynamics of forming the yields of different agro-ecological categories for the future for the period from 2021 to 2050 have been considered. Expected meteorological indicators for the future were calculated using RCP2.6, RCP6.0, RCP4.5 and RCP8.5 climate change scenarios. As a research apparatus, the model for assessing agro-climatic conditions, developed by A. M. Polevoy, was used. Based on the calculations of average long-term agro-climatic indicators of forming agro-ecological categories of sorghum yield and cal-culations of climate change scenarios for the period from 2021 to 2050, it can be noted that according to scenario periods as compared with the actual ones during many-year period, significant changes in tempera-ture and moisture supply of sorghum in growing period will be expected in case of implementing any of sce-narios. It has been established that the deviations of temperature indicators will be insignificant, but these indicators have been determined for a long period, which contains the last years of the previous century and the beginning of this century, when temperature rise has already occurred. Therefore, further changes in temperature and moistening will not contribute to the creation of favorable conditions for sorghum cultiva-tion. Better conditions for plant development and sorghum yield formation are expected in case of RCP2.6 and RCP6.0 scenarios. These conditions are almost the same in both scenarios, which will favor the increase in the expected sorghum grain yield. Under the implementation of RCP4,5 and RCP8.5 scenarios, unfavora-ble agro-environmental conditions are expected for sorghum cultivation as a result of increased drought, which will lead to a decrease in yield as compared with many-year average yield by 3–4 hundredweight/ha. The most unfavorable conditions for the formation of sorghum productivity are expected in case of RCP8.5 scenario, under which grain yield will not exceed 88 % of many-year average one. It will be promising to grow sorghum to obtain green mass, which can be used both as animal feed and as a raw material for biofu-el production.